Bacterial Vaginosis and Premature Uterine Contraction among Women in Ramadi City - Al-Jobori, Wassan A.H. (Journal of the Faculty of Medicine Baghdad, 2008)
Background : To study the incidence of premature uterine contraction (PUC) with bacterial vaginosis (BV) in Ramadi city and to correlate the incidence of (PUC) with severity (grades of BV). Patients and Methods: A prospective study was performed involving 250 women who consecutively attended Gynecological ward in Maternity and Child Hospital. 150 women were control groups (without uterine contraction), and 100 women were regarded as patients group (with uterine contraction) at 28-34 weeks of gestation. BV was diagnosed on the basis of four diagnostic criteria; vaginal pH>4.7, homogenous vaginal discharge, a positive Whiff test, and the presence of clue cells. Results: A total of 250 high vaginal specimens, BV were diagnosed in 74% of cases with PUC (patient group); the incidence was 8% in grade I (GI), 29% in GII, and 37% in GIII. BV was 10% of cases without uterine contraction (control group). Conclusions: There was statistically significant correlation between BV and PUC up to 74%. The incidence and severity of PUC increased with increasing the severity of BV. The patients who used more IUCD (intrauterine contraceptive device), higher reproductive ability, used vaginal douching, and have history of PID (pelvic inflammatory disease) are more liable to have BV and more liable to have PUC.